2015
DOI: 10.1186/s12863-015-0209-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and detection of quantitative trait loci for minerals in Danish Holstein and Danish Jersey milk

Abstract: BackgroundBovine milk provides important minerals, essential for human nutrition and dairy product quality. For changing the mineral composition of the milk to improve dietary needs in human nutrition and technological properties of milk, a thorough understanding of the genetics underlying milk mineral contents is important. Therefore the aim of this study was to 1) estimate the genetic parameters for individual minerals in Danish Holstein (DH) (n = 371) and Danish Jersey (DJ) (n = 321) milk, and 2) detect gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 31 publications
6
46
2
Order By: Relevance
“…The same authors found these wavelengths phenotypically associated with FT-IR-predicted Fat% (2,518 cm −1 ) and lactose percentage (2,587 cm −1 ); however, the same wavelengths were not associated with FTIR-predicted Prot%. In the study by Wang and Bovenhuis (2018), wavenumbers 2,518 and 2,587 cm −1 were associated with several SNP in a sub-region of chromosome 1 of the bovine genome where a QTL for the concentration of phosphorus in milk has been reported (SLC37A1, Buitenhuis et al, 2015;Kemper et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The same authors found these wavelengths phenotypically associated with FT-IR-predicted Fat% (2,518 cm −1 ) and lactose percentage (2,587 cm −1 ); however, the same wavelengths were not associated with FTIR-predicted Prot%. In the study by Wang and Bovenhuis (2018), wavenumbers 2,518 and 2,587 cm −1 were associated with several SNP in a sub-region of chromosome 1 of the bovine genome where a QTL for the concentration of phosphorus in milk has been reported (SLC37A1, Buitenhuis et al, 2015;Kemper et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…One may question whether observing such differences between datasets indicated group specific allele effects, or simply group differences in terms of statistical power due to a difference in allele frequency. This question often arises when GWAS is applied separately to genetic groups, as in maize [16,56] or dairy cattle [57,58], and is very difficult to answer except for obvious configurations such as associations at SNPs segregating only in one group.…”
Section: Accounting For Genetic Groups In Gwasmentioning
confidence: 99%
“…Milk mineral (Ca, Se, K, Mg, P, and Zn) concentrations in the Dutch milk samples were determined by inductively coupled plasma-atomic emission spectrometry (ICP-AES; Vista Axial, Varian, Australia) on whole milk as described by van Hulzen et al (2009). For the Danish milk samples, milk minerals (Ca, Se, K, Mg, P, and Zn) were extracted from skim milk by acid sonication and identified using inductively coupled plasma mass spectrometry (ICP-MS) as described by Buitenhuis et al (2015).…”
Section: Mineral Contentsmentioning
confidence: 99%